Perbandingan Sumber-Sumber Hukum dan Karakteristiknya dalam Kajian Syariah dan Perundang-Undangan - ‎ ‎ ‎, Ja'far Shodiq; Muhammad Syakir Al Kautsar (Institut Agama Islam Negeri Metro, 2022)
This research examines the comparison between conventional pawning and sharia pawning in the context of Indonesian law. Using library research methods, this study analyzes legal sources, characteristics, operational mechanisms, as well as views of Islamic law and legislation on pawnshop practices. The research results show that although there are similarities in several aspects, sharia and conventional pawning have fundamental differences in their operational principles and legal basis. Sharia pawning is based on the Koran, Hadith and ulama fatwas, and operates without the element of usury, while conventional pawning is regulated in the Civil Code and applies an interest system. This study also outlines the rights and obligations of the parties involved in pawn transactions, as well as the risks and benefits that accompany them. In conclusion, although both aim to meet people's needs for loans with collateral, sharia pawning offers an alternative that is more in line with Islamic principles in transactions.